Determinants of Quality of Life Air Traffic Controller in AirNav Surabaya - Muhammad Fandi Ahmad; Lalu Muhammad Saleh; Yahya Thamrin; Syamsiar S. Russeng; Saifuddin Sirajuddin; Agus Bintara Birawida (Indian Journal of Forensic Medicine & Toxicology, 2022)
The quality of work life is affected by the quality of the work environment. A positive work atmosphere will create a conducive work life. This study aims to determine the factors that affect the quality of life of air traffic controller at AirNav Surabaya. This is a quantitative research with a cross sectional study method. Interviews were conducted on 38 workers who were drawn based on the purposive sampling method. Then, from these results a logistic regression test was carried out which showed that blood pressure, position, and workload had a significant relationship. To determine the effect of individual characteristics, work fatigue and quality of life were measured using a questionnaire, blood pressure using a tensimeter and workload using an oximeter. Data were analyzed using the SPSS 25 application with the chi-square test. Results of the chi-square test analysis showed that there was a relationship between age and quality of life (p = 0.009), blood pressure with quality of life (p = 0.032), years of service with quality of life (p = 0.031), position and quality of life (p = 0.029), fatigue with quality of life (p = 0.012) and workload with quality of life (p = 0.005), while there was no relationship between sex and quality of life (0.279) and marital status with quality of life (p = 0.560). From these results, a logistic regression test was carried out which showed that blood pressure, position, and workload had a significant relationship. This research suggests AirNav Surabaya to pay more attention to the quality of life of air traffic controller, maintain the nutritional intake, exercise regularly, and pay attention to rest times.